1997
DOI: 10.1074/jbc.272.28.17405
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Four Amino Acids in the Gastrin-releasing Peptide Receptor That Are Required for High Affinity Agonist Binding

Abstract: The bombesin family of G-protein-coupled receptors includes the gastrin-releasing peptide receptor (GRP-R), the neuromedin B receptor (NMB-R), bombesin receptor subtype 3 (BRS-3), and bombesin receptor subtype 4 (bb4). All species homologues of GRP-R, NMB-R, and bb4 bind bombesin with dissociation constants in the nanomolar range; by comparison, human BRS-3 binds bombesin at much lower affinity (K d > 1 M). We used this difference to help identify candidate residues that were potentially critical for forming t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 24 publications
(22 reference statements)
4
54
0
Order By: Relevance
“…Moreover, Liebow et al showed that bombesin and EGF seemed to promote phosphorylation of similar substrates (Liebow et al, 1994). Bombesin, which binds with high affinities to multiple BLP receptors, including NMBR and bombesin receptor subtype 4 (Akeson et al, 1997), has been shown to transactivate EGFR in the PC-1 prostate cancer cell line (Prenzel et al, 1999). However, the biologic consequences of bombesin-induced EGFR trans;-activation in prostate cancer were not investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Liebow et al showed that bombesin and EGF seemed to promote phosphorylation of similar substrates (Liebow et al, 1994). Bombesin, which binds with high affinities to multiple BLP receptors, including NMBR and bombesin receptor subtype 4 (Akeson et al, 1997), has been shown to transactivate EGFR in the PC-1 prostate cancer cell line (Prenzel et al, 1999). However, the biologic consequences of bombesin-induced EGFR trans;-activation in prostate cancer were not investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The human hBRS-3 cDNA was inserted into pcDNA3.1 ϩ at the EcoRI site, and BRS-3 mutant receptors were constructed by using the QuikChange Site-Directed Mutagenesis Kit, following the manufacturer's instructions, with minor modifications. The mouse GRPR used in this study was identical to that described previously (Fathi et al, 1993a;Akeson et al, 1997). Nucleotide sequence analysis of the entire coding region was performed.…”
Section: Methodsmentioning
confidence: 99%
“…The human BB 1 receptor (Moody et al, 1986(Moody et al, , 1992(Moody et al, , 1995aCorjay et al, 1991;Benya et al, 1995b), as well as the rat BB 1 receptor Jones et al, 1992;Wang et al, 1992;Dobrzanski et al, 1993;Lach et al, 1995;Akeson et al, 1997;Tsuda et al, 1997b;Vigne et al, 1997;Hou et al, 1998) is coupled to phospholipase C, resulting in breakdown of phosphoinositides, mobilization of cellular calcium, and activation of protein kinase C. BB 1 receptor activation also results in the stimulation phospholipase A 2 (Moody et al, 1995a) and phospholipase D by a PKC-dependent and -independent mechanism (Tsuda et al, 1997b) but does not activate adenylate cyclase (Benya et al, 1992). BB 1 receptor stimulation also results in activation of tyrosine kinases (Lach et al, 1995;Tsuda et al, 1997b) stimulating tyrosine phosphorylation of p125…”
Section: G Bb 1 Receptor Signaling Activation and Modulatorymentioning
confidence: 99%